2011
DOI: 10.1080/15374416.2011.563473
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Adolescent Mother–Grandmother Psychological Conflict During Early Parenting and Children's Problem Behaviors at Age 7

Abstract: This study extends the determinants of parenting model to adolescent mothers by examining how adolescent mother–grandmother psychological conflict and perceptions of infant fussiness from birth through age 2 years relate to children's problem behaviors at age 7. Participants were 181 adolescent mother, child, and grandmother triads living in multigenerational households and recruited at delivery. Psychological conflict was characterized by two stable trajectories. In multivariate models that included maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…For example, Sellers et al (2011) demonstrated that when low-income African American adolescent mothers reported low levels of mother-grandmother conflict, they were observed to use less negative control and more nurturing parenting when interacting with their toddlers. Further, Buckingham-Howes, Oberlander, Hurley, Fitzmaurice, and Black (2011), in a related study from the same sample, found that trajectories of self-reported adolescent mother-grandmother conflict from birth to 24 months were linked to elevated grandchild externalizing behaviors at age 7. The applicability of this pattern of family spillover effects to nonadolescent mothers is unclear, however.…”
Section: Adolescent Mother-grandmother Relationshipsmentioning
confidence: 89%
“…For example, Sellers et al (2011) demonstrated that when low-income African American adolescent mothers reported low levels of mother-grandmother conflict, they were observed to use less negative control and more nurturing parenting when interacting with their toddlers. Further, Buckingham-Howes, Oberlander, Hurley, Fitzmaurice, and Black (2011), in a related study from the same sample, found that trajectories of self-reported adolescent mother-grandmother conflict from birth to 24 months were linked to elevated grandchild externalizing behaviors at age 7. The applicability of this pattern of family spillover effects to nonadolescent mothers is unclear, however.…”
Section: Adolescent Mother-grandmother Relationshipsmentioning
confidence: 89%
“…However, only recently have studies prospectively modeled maternal depressive symptoms (Campbell et al 2009;Gump et al 2009;Cambron et al 2010;Ferro et al 2011a, b;Lo et al 2010;Marmorstein 2010;Mazza et al 2010;Wickrama and Wickrama 2010;Buckingham-Howes et al 2011). Two obstacles that prevented such exploration were a lack of longitudinal data at the individual level and lack of statistical methods that could provide a richer understanding of changes in depressive symptoms over time.…”
Section: Introductionmentioning
confidence: 97%
“…Despite emerging interest, research examining the psychological well-being of adolescents confronting fatherhood still lags far behind the extensive studies characterizing the adolescent mothers' experiences ( e.g. Buckingham-Howes et al, 2011; Davis, 2002; Miller-Loncar et al, 1998; Zayas et al, 2002). Extant literature on adolescent fathers has focused primarily on social support and fulfillment of parenting behaviors related to adolescent mothers and their children, including involvement, child support, and financial assistance (Fagan, Bernd, & Whiteman, 2007; Gee & Rhodes, 2003; Saleh & Hilton, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have incorporated many conceptual frameworks to give perspective to adolescents' relationships with their parents, such as attachment theory (Parker and Benson, 2004), the determinants of parenting model (Buckingham-Howes, Oberlander, Hurley, Fitzmaurice, & Black, 2011), and the parental apprentice model (Sellers, Black, Boris, Oberlander, & Myers, 2011). Each framework has its advantage, yet the Convoy Model of Social Support (Antonucci, 1986) uses a unique developmental approach to describe the social convoy as a protective network of support that changes in structure as the person develops throughout life.…”
Section: Introductionmentioning
confidence: 99%